THE POLITENESS AND GESTURE STRATEGY STAFF IN FRONT OFFICE OF MEGALAND HOTEL SURAKARTA - RAHMAD, FATHONI; ZANAH, SRI WAHYUNI SAMARATUL (Politeknik Harapan Bangsa Surakarta, 2020)
The purpose of this research is : To know the mistake of politeness and gesture of front office staff of Megaland Hotel Solo when serving foreign guest. And to find out the problems affecting the faults by front office staff related to the use of English with foreign guests through an interview on WhatsApp Messenger. The Writing of this report is presented descriptively to obtain an overview of various information relating to the provision of services to hotel guests. methods of collecting and using documentation, direct observation, interviews and literature study are data from apprentices described in sentence form. The data obtained are then analyzed and presented descriptively. The results show that the front office department of Megaland Hotel Solo has a significant role in providing services to guests, as the front office department has direct contact and will give first and last impression to the upcoming guest. Internship results can be seen that the quality of front office staff services consisting of the speed of service, the accuracy of the service and the hospitality service has been well done by the hotel front desk staff, but it is better for the front office staff to master the correct English, polite and good gesture. especially for foreign guests interested in returning to stay at Megaland Hotel Solo.